Decreased Water Mobility Contributes To Increased α‐Synuclein Aggregation. (12th January 2023) - Stephens, Amberley D.; Kölbel, Johanna; Moons, Rani; Chung, Chyi Wei; Ruggiero, Michael T.; Mahmoudi, Najet; Shmool, Talia A.; McCoy, Thomas M.; Nietlispach, Daniel; Routh, Alexander F.; Sobott, Frank; Zeitler, J. Axel; et al.
Abstract: The solvation shell is essential for the folding and function of proteins, but how it contributes to protein misfolding and aggregation has still to be elucidated. We show that the mobility of solvation shell H2 O molecules influences the aggregation rate of the amyloid protein α‐synuclein (αSyn), a protein associated with Parkinson's disease. When the mobility of H2 O within the solvation shell is reduced by the presence of NaCl, αSyn aggregation rate increases. Conversely, in the presence CsI the mobility of the solvation shell is increased and αSyn aggregation is reduced. Changing the solvent from H2 O to D2 O leads to increased aggregation rates, indicating a solvent driven effect. We show the increased aggregation rate is not directly due to a change in the structural conformations of αSyn, it is also influenced by a reduction in both the H2 O mobility and αSyn mobility. We propose that reduced mobility of αSyn contributes to increased aggregation by promoting intermolecular interactions. Abstract : Ions can influence the mobility of water molecules in the solvation shell of a protein, which is important for folding and function. We show ions that decrease water mobility contribute to decreased protein mobility and subsequently to an increase in the self‐association and aggregation rate. Alteration in water mobility may occur in ageing cells where ion concentrations become dysregulated and therefore promote αSyn aggregation.